Carbonate-Based Lanthanum Strontium Cobalt Ferrite (LSCF)–Samarium-Doped Ceria (SDC) Composite Cathode for Low-Temperature Solid Oxide Fuel Cells - Muhammed Ali S.A.; Jarot Raharjo; Mustafa Anwar; Deni Shidqi Khaerudini; Andanastuti Muchtar; Luca Spiridigliozzi; Mahendra Rao Somalu (Applied Sciences, 2020)
Perovskite-based composite cathodes, La0.6Sr0.4Co0.2Fe0.8O3-δ (LSCF)–Ce0.8Sm0.2O1.9-carbonate (SDCC), were investigated as cathode materials for low-temperature solid-oxide fuel cells. The LSCF was mixed with the SDC–carbonate (SDCC) composite electrolyte at different weight percentages (i.e., 30, 40, and 50 wt %) to prepare the LSCF–SDCC composite cathode. The effect of SDCC composite electrolyte content on the diffraction pattern, microstructure, specific surface area, and electrochemical performances of the LSCF–SDCC composite cathode were evaluated. The XRD pattern revealed that the SDCC phase diffraction peaks vary according to its increasing addition to the system. The introduction of SDCCs within the composite cathode did not change the LSCF phase structure and its specific surface area. However, the electrical performance of the realized cell drastically changed with the increase of the SDCC content in the LSCF microstructure. This drastic change can be ascribed to the poor in-plane electronic conduction at the surface of the LSCF cathode layer due to the presence of the insulating phase of SDC and molten carbonate. Among the cathodes investigated, LSCF–30SDCC showed the best cell performance, exhibiting a power density value of 60.3–75.4 mW/cm2 at 600 °C to 650 °C.